Evolution of Land use and occupancy in the municipality of João Monlevade – MG facing pressures on water resources (Research, Society and Development, 2022)
Changes in the use and occupation of land in hydrographic basins in various regions of the planet have resulted in the deterioration of the quality and quantity of water, both surface and underground. In this scenario, studies on the evolution of use and occupation are a great tool to guide public policies and watershed management plans. Thus, this work aimed to carry out, through geoprocessing tools, the evolution of Land Use and Occupation for the municipality of João Molevade, located in the Piracicaba River basin, in the state of Minas Gerais. The file downloaded from MapBiomas, from the years 1990, 2000, 2010 and 2020 was used as a database. The data were cut to the limit of the study area and reclassified into the following typologies: Forest, Non-Forest Natural Formation, Agriculture, Unvegetated area, Water body. During the study period, there was a decrease in the Forest typology and an increase in the Non-Forest Natural Formation typology, these are directly related, since the forest areas were mainly occupied by pastures and by the expansion of the urban area of ​​the municipality. These replacements contribute to reducing the recharge of local aquifers and to the contribution of sediments to surface water bodies, consequences intensified by the rugged relief of the region. In this way, the present work becomes an important subsidy for managers in planning the use and occupation of the basin, as well as serving as a basis for the elaboration of management plans for this basin.